Evaluation of bone apposition on surface modified titanium implant in experimental animal model: A systematic review and meta-analysis - Priya Saini; Shaveta Sood; Gurparkash Singh Chahal; Ashish Jain (Wolters Kluwer Medknow Publications, 2024)
Purpose: To evaluate the response of peri-implant bone to smooth (machined) surface and surface-modified dental implants in healthy experimental animal models. Materials and Methods: Systematic electronic search was done for using PUBMED, SCOPUS, WEB OF SCIENCE, and EMBASE databases for potentially relevant records from the last 20 years. Duplicate screening and data extraction were performed to formulate the evidence tables and meta-analysis following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The outcome criteria were: 1. Bone Implant Contact (BIC) in percentage, 2. Removal Torque Values (RTV) in Ncm, 3. Implant stability Quotient (ISQ), Quality assessment was done using the ARRIVE (Animal Research: Reporting of In Vivo Experiments) guidelines and SYRCLE RoB (Systematic Review Centre for Laboratory Animal Experimentation Risk of Bias) tool. Results: Results were expressed as pooled mean difference for the respective groups viz. sandblasted and acid etched, laser modified, acid etched and anodized surface. The surface modified implants revealed somewhat higher BIC over machined surface (P < 0.01). Forest plot were drawn for all the outcome variables. Conclusions: Within the limitations of this study, the authors found a higher degree of osseointegration pertaining to bone to implant interface, RTV, and implant stability quotient (ISQ) with surface modified procedures which seemed to promote bone formation around peri-implant tissue during the early stages of healing. After analyzing all 37 included publications for the outcome of interest (BIC%, RTV, ISQ), a positive outcome was obtained for both subtractive and additive implant surface modifying procedures over machined implant surfaces when the data were pooled together. More advanced research work on healthy animal models needs to be investigated to review the impact of surface modifications on dental implant osseointegration.